Fine needle aspiration cytology of thyroid swellings: Experience in a tertiary care hospital of Nepal (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Fine Needle Aspiration Cytology (FNAC) being a minimally invasive technique, is particularly suitable in the sensitive neck area. FNAC can obviate the need for surgery if the lesion is shown to be non neoplastic or if it confirms suspected recurrent tumor. A preoperative cytological diagnosis of a primary neoplasm of thyroid may allow more rational    planning of surgery.Method: This descriptive observational study was carried out at the Department of ENT- Head & Neck Surgery, Gandaki Medical College and Charak Hospital, Pokhara, Nepal, from August 2010 to November 2011. A total of 154 consecutive FNAC of thyroid swellings was included.Results: Out of 154 patients female were 142 (92%) and men were 12 (8%). In this series of 154 thyroid swellings on FNAC one hundred and thirty six (88%) were non neoplastic and eighteen (12%) neoplastic. Among non neoplastic thyroid swelling, adenoma was the most common sixty two (40%), followed by colloid cyst, Hashimoto thypoiditis, subacute thyroiditis, adenoma, cystic lesion, Gravess disease, thyroglossal cyst and lymphocytic thyroiditis. Among neoplastic thyroid swelling papillary carcinoma was the commonest nine (5.8%) followed by follicular neoplasm six (3.9%).Conclusion: It is concluded from the present study that female in our region were more affected, non-neoplastic lesions of the thyroid were more common (colloid goiter being the commonest) than neoplastic lesions (papillary carcinoma being the commonest). DOI:http://dx.doi.org/10.3329/bjo.v18i2.11984 Bangladesh J Otorhinolaryngol 2012; 18(2): 119-123